MANAGEMENT OF IRRIGATION AND NITROGEN FERTILIZERS TO REDUCE AMMONIA VOLATILIZATION - Viero,Fernando (2015)
ABSTRACT Nitrogen losses by ammonia (NH3) volatilization can be reduced by appropriate irrigation management or by alternative N sources, replacing urea. The objective of this study was to evaluate the efficiency of irrigation management and N source combinations in decreasing NH3 volatilization from an Argissolo Vermelho Distrófico típico cultivated for 28 years with black oat (Avena strigosa) and maize (Zea mays), under no-tillage in the region of Depressão Central, Rio Grande do Sul, Brazil. The experiment was arranged in a randomized block design with split plots with three replications, where the main plots consisted of irrigation systems: no irrigation; irrigation immediately before and irrigation immediately after fertilization. The subplots were treated with different N sources: urea, urea with urease inhibitor and slow-release fertilizer, at an N rate of 180 kg ha-1, broadcast over maize, plus a control treatment without N fertilization. Ammonia volatilization was assessed using semi-open static collectors for 1, 2, 4, 6, and 10 days after N fertilization. In general, more than 90 % of total NH3-N losses occurred until three days after N fertilization, with peaks up to 15.4 kg ha-1 d-1. The irrigation was efficient to reduce NH3 losses only when applied after N fertilization. However, reductions varied according to the N fertilizer, and were higher for urea (67 %) and slightly lower for urea with urease inhibitor (50 %) and slow-release fertilizer (40 %), compared with the mean of the treatments without irrigation and irrigation before fertilization. The use of urea with urease inhibitor instead of urea was only promising under volatilization-favorable conditions (no irrigation or irrigation before N fertilization). Compared to urea, slow-release fertilizer did not reduce ammonia volatilization in any of the rainfed or irrigated treatments.